IPod : the missing manual - Biersdorfer, J. D. (Missing manual., 2006)
With iPod and iTunes, Apple's gotten the world hooked on portable music, pictures, and videos. One thing they haven't delivered, though, is an easy guide for getting the most from your sleek little entertainment center. Enter iPod: The Missing Manual, 5th Edition-a book as breathtaking and satisfying as its subject. Our latest edition thoroughly covers the redesigned iPod Nanos, the video iPod, the tiny Shuffle and the overhauled iTunes 7. Each custom-designed page sports easy-to-follow color graphics, crystal-clear explanations, and guidance on the most useful things your iPod can do. Topic.